Face of a fighter: Bizygomatic width as a cue of formidability. Issue 4 (6th June 2014) - Zilioli, Samuele; Sell, Aaron N.; Stirrat, Michael; Jagore, Justin; Vickerman, William; Watson, Neil V.
Abstract : Humans can accurately extract information about men's formidability from their faces; however, the actual facial cues that inform these judgments have not been established. Here, through three studies, we test the hypothesis that bizygomatic width (i.e. facial width‐to‐height ratio, fWHR) covaries with actual physical formidability ( hypothesis #1 ) and that humans use this cue when making assessments of formidability ( hypothesis #2 ). Our data confirm that fWHR is predictive of actual fighting ability among professional combatants (study 1). We further show that subjects' assessments of formidability covary with the target's fWHR on natural faces (study 2), computer‐generated images of strong and weak faces (study 2), and experimentally manipulated computer‐generated faces (study 3). These results support the hypothesis that bizygomatic width is a cue of formidability that is assessed during agonistic encounters. Aggr. Behav. 41:322–330, 2015. © 2014 Wiley Periodicals, Inc.